Effectiveness of Health Education Intervention in Improving Knowledge, Attitude, and Practices Regarding Tuberculosis Among Nurses Working in Tuberculosis Centers in Libya - Elbahloul, Muftah; Khadija Ali,; Sana Alghennai, (AlQalam Journal of Medical and Applied Sciences, 2023)
Background and aims. Nurses make up by far the largest group of healthcare workers in any part of the world, playing an important role in the direct management of tuberculosis (TB) patients and facing a high risk of infection. The aim of this study was to assess the impact of a health educational intervention on knowledge, attitude and practice of the nurses working in TB centres in Libya. Methods. A sample of 100 TB nurses was randomly allocated into intervention and control groups. The intervention group received health education regarding tuberculosis using a developed module over a period of 3 days at Tripoli Tuberculosis, while the control group did not receive any education. Knowledge and attitude scores for both groups were evaluated using a self-administered validated questionnaire at baseline, immediate after intervention, three, and six months. Practice score was assessed only at baseline, three, and six months. Results. The TB educational intervention program was found to be effective immediately after intervention, as the knowledge score improved by 40.08 (95% CI 41.77, 38.39) (p-value < 0.001) among the intervention group. The knowledge scores remained stable at 3-month and 6-month follow-up. Likewise, there was significant improvement in attitude score with a mean difference of 1.769 (95% CI 1.88, 1.65) (p < 0.001). The attitude scores remained stable at 3-month and 6-month follow-up. Similarly, there was improvement in practice score with a mean difference of 18.23 (95% CI 16.12, 0.17.43) (p < 0.001). The practice scores remained stable at 6-month follow-up. Conclusions. The educational intervention carried out was effective in improving the nurses’ knowledge, attitude and practice towards TB over time. Therefore, tuberculosis education programme should become part of nursing development program and the regular activities undertaken by all nurses in colleges, institutes and hospitals in Libya.